Respiratory dysbiosis in cats with spontaneous allergic asthma - Vientós-Plotts, Aida I.; Ericsson, Aaron C.; McAdams, Zachary L.; Rindt, Hansjorg; Reinero, Carol R. (Frontiers in Veterinary Science, 2022)
Deviations from a core airway microbiota have been associated with the development and progression of asthma as well as disease severity. Pet cats represent a large animal model for allergic asthma, as they spontaneously develop disease similar to atopic childhood asthma. This study aimed to describe the lower airway microbiota of asthmatic pet cats and compare it to healthy cats to document respiratory dysbiosis occurring with airway inflammation. We hypothesized that asthmatic cats would have lower airway dysbiosis characterized by a decrease in richness, diversity, and alterations in microbial community composition including identification of possible pathobionts. In the current study, a significant difference in airway microbiota composition was documented between spontaneously asthmatic pet cats and healthy research cats mirroring the finding of dysbiosis in asthmatic humans. Filobacterium and Acinetobacter spp. were identified as predominant taxa in asthmatic cats without documented infection based on standard culture and could represent pathobionts in the lower airways of cats. Mycoplasma felis, a known lower airway pathogen of cats, was identified in 35% of asthmatic but not healthy cats.